2001
DOI: 10.1016/s0022-5347(05)65671-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the Tunica Albuginea in Congenital Penile Curvature

Abstract: Our results show that ultrastructural changes in the tunica albuginea may cause congenital penile curvature, possibly by altering mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The cause of penile curvature is unknown but might be triggered by changes in the tissue structure of the tunica albuginea 4 . Ventral curvature is considered the most common 5 and in our series, 29/49 patients (59.1%) had ventral or left ventrolateral curvature.…”
Section: Discussionmentioning
confidence: 54%
“…The cause of penile curvature is unknown but might be triggered by changes in the tissue structure of the tunica albuginea 4 . Ventral curvature is considered the most common 5 and in our series, 29/49 patients (59.1%) had ventral or left ventrolateral curvature.…”
Section: Discussionmentioning
confidence: 54%
“…However, recent histopathologic studies have revealed that CPC is caused by abnormal development of the tunica albuginea of the corpora cavernosa and increased elasticity of tunica on the longer side, rather than urethral anomalies or short urethrae ( 13 ). In cases with ventral curvatures, asymmetric corporal development is responsible and the urethra is mostly normal, but in cases with lateral, dorsal or mixed curvatures, the abnormal development is always on the convex side of the tunica albuginea.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of fibrin in the human PD plaque even months after development of the plaque, as has been previously shown by histochemical staining [6], is very characteristic of the human condition and we confirm by immunodetection the presence of fibrin, or its precursor, fibrinogen, in the plaque. The injection of fibrin alone into the TA of the rat can elicit a lesion characterized by oedema and inflammation followed by tunical thickening, collagen disorganization, elastin fragmentation, and increased TGF-b 1, ROS, ASMA and iNOS expression, as is seen in both human PD and the TGF-b 1-induced animal model of PD [7][8][9][11][12][13][14][15]. This supports the hypothesis that fibrin deposition after trauma to the penis could be the primary event triggering the expression of pro-fibrotic factors like TGF-b 1 that would lead to the development of a tunical plaque.…”
Section: Discussionmentioning
confidence: 99%